Influence of incorporation of ZnO nanoparticles and biaxial orientation on mechanical and oxygen barrier properties of polypropylene films for food packaging applications - Lepot, N; Van Bael, M.K; Van den Rul, H; D'Haen, J; Peeters, R; Franco, D; Mullens, J (Journal of applied polymer science, 2011)
In this work, the effect of zinc oxide (ZnO) concentration and shape on processing and properties of new biaxially oriented polypropylene (BOPP)-ZnO nanocomposites was studied. The use of spherical nanoparticles and nanorods was expected to differently influence the properties of the final material. Films of isotactic polypropylene prepared with different ZnO incorporation were biaxially oriented under conditions of temperature and strain rate that were similar to those encountered in a commercial film process. Scanning electron microscopy analysis was performed to visualize the dispersion degree of the ZnO nanoparticles in the polymer matrix and to observe the surface and the orientation of the elongated nanoparticles. Furthermore, the prepared ZnO-BOPP nanocomposites were evaluated for both mechanical and oxygen barrier property enhancement. A good combination of mechanical and oxygen barrier properties was obtained for the ZnO-BOPP films. This result makes the ZnO-BOPP nanocomposite a proper material for applications such as food packaging.